THE EFFECT OF WORK MOTIVATION, WORK DISCIPLINE, AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE: CASE STUDY AT CV. ATH GROUP BALIKPAPAN - Maulidiyah, Lailatul; Sidi, Agus Purnomo (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
Organizational success depends on employee performance, which is impacted by a number of variables such work environment, discipline, and motivation. This study looks into how these elements affect ATH GROUP Balikpapan employees' job performance. The study uses a quantitative methodology using Partial Least Squares (PLS) with Smart PLS 3 to assess the connections between the dependent variable, job performance, and the independent variables, work motivation, work discipline, and the work environment. One hundred employees were given a questionnaire to complete in order to gather data, and Structural Equation Modeling (SEM) was used in the study to determine how significant the associations were. The results indicate that all three factors significantly influence job performance, with p-values < 0.05 for each path coefficient. Work motivation demonstrated the strongest positive impact, followed by the work environment and work discipline. The findings emphasize the direct and indirect effects of these variables, highlighting their synergistic contributions to enhancing employee productivity. With a high R2 value of 0.836, the model is able to explain 83.6% of the variation in job performance. To sum up, encouraging motivation, implementing just disciplinary procedures, and creating a positive work atmosphere are all critical tactics for raising employee performance. These results offer insightful information to businesses looking to maximize employee productivity and succeed over the long haul.